THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON FIRM VALUE WITH PROFITABILITY AS A MODERATING VARIABLE - Ida Ayu Made Sukma Dewi; I Made Pande Dwiana Putra (Adisam Publisher, 2025)
This study aims to provide empirical evidence on the effect of corporate social responsibility (CSR) disclosure on firm value, with profitability as a moderating variable. The object of this study is energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This research is grounded in signaling theory as the main theoretical framework and is supported by contingency theory to explain the moderating role of profitability in the relationship between CSR disclosure and firm value. The sample was selected using a purposive sampling method, resulting in 22 companies with a total of 66 observations over a three-year period. The analytical technique employed is Moderated Regression Analysis (MRA). The findings reveal that CSR disclosure has a positive effect on firm value, and that profitability strengthens the effect of CSR disclosure on firm value.